A Michael addition–cyclization-based switch-on fluorescent chemodosimeter for cysteine and its application in live cell imaging. (2nd March 2018) - Manna, Srimanta; Karmakar, Parthasarathi; Ali, Syed Samim; Guria, Uday Narayan; Sarkar, Ripon; Datta, Pallab; Mandal, Debasish; Mahapatra, Ajit Kumar
Abstract : We designed and synthesized a fast response fluorescent probe, BTAC (benzothiazol-azacoumarin), for detection of cysteine (Cys). Abstract : Based on a conjugate addition/intramolecular cyclization sequence, we designed and synthesized a fast response fluorescent probe, BTAC (benzothiazol-azacoumarin), for the discriminative detection of cysteine (Cys). The reaction of cysteine withBTAC results in the cleavage of the acrylate moiety fromBTAC, thereby producingBTAC-OH, with a remarkable fluorescence enhancement at 560 nm. The probe exhibits high sensitivity and selectivity toward cysteine over homocysteine and glutathione and the detection limit reached as low as 124 nM for cysteine. The addition of Cys resulted in the color of the solution ofBTAC changing from colorless to greenish yellow under the simulation of physiological conditions andBTAC could serve as a "naked-eye" indicator. The structure ofBTAC was established by computational DFT (density functional theory) calculation and time dependent density functional theory (TDDFT) calculations were performed to demonstrate the electronic properties ofBTAC and its product, BTAC-O − . Finally, the probe was successfully applied for the fluorescence bioimaging of cysteine owing to its photostability and low cytotoxicity.